COMPARATIVE ANALYSIS OF DENTAL CARIES IN CHILDREN WITH NEUROPSYCHIATRIC DISORDERS AND CONGENITAL CLEFT OF LIP AND PALATE LIVING IN KRASNODAR - O. V. GULENKO; V. V. VOLOBUEV; A. F. VERAPATVELIAN; A. S. GRACHEVA; A. S. GUMENYUK; Y. A. VASILEV (Кубанский научный медицинский вестник)
Examined three groups of children aged 6 to 17 years: the first 96 children with CCLP (congenital cleft of lip and/or palate), the second 112 children with neuropsychiatric disorders (NPD) and the third (control) 86 somatically healthy children. On the basis of the index of KPU + kp and KPU in children with CCLP and in children with NPD high rates of prevalence and intensity of dental caries were found compared with the control group. The highest rates of prevalence of dental caries were found in children with CCLP and intensity of dental caries in children with NPD that is the most prominent in the children with NPD at the age from 6 to 12 years old. In children with CCLP and in children with NPD, the level of oral hygiene has significantly worse values compared to the control, which suggests the possibility of preventing tooth decay through improving oral hygiene of the mouth. The lowest level of oral hygiene was observed in children with CCLP that is mediated by severe congenital pathology.